2020
DOI: 10.3390/ijms21165616
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Long Noncoding RNA LNC-EPHA6 Associates with Acute Rejection after Kidney Transplantation

Abstract: Acute rejection (AR) of a kidney graft in renal transplant recipients is associated with microvascular injury in graft dysfunction and, ultimately, graft failure. Circulating long noncoding RNAs (lncRNAs) may be suitable markers for vascular injury in the context of AR. Here, we first investigated the effect of AR after kidney transplantation on local vascular integrity and demonstrated that the capillary density markedly decreased in AR kidney biopsies compared to pre-transplant biopsies. Subsequently, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The loss of the microvasculature, also referred to as microvascular rarefaction, is a critical determinant in kidney disease states such as acute kidney failure, diabetic nephropathy or kidney transplant rejection (53). The resulting ischaemia is a driver for an inflammatory This article is protected by copyright.…”
Section: Kidney: the Coagulome In Kidney Diseasementioning
confidence: 99%
“…The loss of the microvasculature, also referred to as microvascular rarefaction, is a critical determinant in kidney disease states such as acute kidney failure, diabetic nephropathy or kidney transplant rejection (53). The resulting ischaemia is a driver for an inflammatory This article is protected by copyright.…”
Section: Kidney: the Coagulome In Kidney Diseasementioning
confidence: 99%
“…Therefore, measuring the levels of dmtDNA could be a valuable method for predicting acute rejection in individuals who have undergone kidney transplantation. In a study by Groeneweg et al [ 70 ], the influence of acute rejection (AR) on local vascular integrity was examined in 47 kidney-transplant recipients by analyzing kidney biopsies. The researchers observed a reduction in capillary density during AR.…”
Section: Genetic Markersmentioning
confidence: 99%
“…For examples, circulating LNC-EPHA6 was con rmed as a promising marker for vascular injury under acute rejection after kidney transplantation [19]. Another study reported that lncRNA NEAT1 served as a sponge for miR-146b to regulate TRAF6 expression and NF-κB signaling, thus accelerating renal mesangial cell injury in lupus nephritis [20].…”
Section: Introductionmentioning
confidence: 99%